2014
DOI: 10.1021/nn5049987
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination among Protein Variants Using an Unfoldase-Coupled Nanopore

Abstract: Previously we showed that the protein unfoldase ClpX could facilitate translocation of individual proteins through the α-hemolysin nanopore. This results in ionic current fluctuations that correlate with unfolding and passage of intact protein strands through the pore lumen. It is plausible that this technology could be used to identify protein domains and structural modifications at the single-molecule level that arise from subtle changes in primary amino acid sequence (e.g., point mutations). As a test, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
125
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(126 citation statements)
references
References 67 publications
1
125
0
Order By: Relevance
“…Activity has begun in this area of nanopore proteomics [71,72], and there is a pressing need for improved means to translocate polypeptide chains through pores. A long-term goal is to characterize proteins from single cells.…”
Section: Applications Of Engineered Poresmentioning
confidence: 99%
“…Activity has begun in this area of nanopore proteomics [71,72], and there is a pressing need for improved means to translocate polypeptide chains through pores. A long-term goal is to characterize proteins from single cells.…”
Section: Applications Of Engineered Poresmentioning
confidence: 99%
“…Although several studies utilizing peptide and protein translocation through nanopores, have been published over the last several years [4749,5458], direct method for validating peptide translocations are lacking. A recent publication tried to solve the problem by conjugating a single-stranded DNA to unfolded protein and then amplify the DNA using PCR after translocation[69].…”
Section: Discussionmentioning
confidence: 99%
“…3). 12 Analysis of the current showed that its temporal sequence was repeatable and able to be associated with pre-unfolding and translocation events of the four domains of the protein.…”
Section: Protein Folding Studied With Unfoldase-coupled Nanoporesmentioning
confidence: 97%